Development, implementation and evaluation an empowerment program for adolescent girls with substance use disorders: Protocol for a mixed methods study - Zakiye Ghelbash; Mousa Alavi; Mahnaz Noroozi; Masuood Mahdavianfar (Journal of Education and Health Promotion)
BACKGROUND: A tendency to high-risk behaviors, such as suicide, high-risk sexual behavior, and violence are among the important consequences of substance use in adolescent girls. Today, programs are designed with an empowerment approach, as important practical strategies for the management of issues associated with health and social welfare. Thus, in this study, we intend to design a comprehensive psychosocial empowerment program with an approach to reducing high-risk behaviors in adolescent girls with substance use disorder. MATERIALS AND METHODS: Using the Talbot and Verrinder model, this study will be designed in six steps. In the first step, the experiences of adolescent girls with substance use disorder as well as their psychosocial needs will be identified using a qualitative approach. Then, through a review of the literature, the needs and strategies will be completed and enriched. Thereafter, using a Delphi technique, the relevant needs and strategies identified in previous stages will be prioritized. In the second step, the program’s draft will be designed based on the results obtained from the previous step. During the third phase, the content of the program will be evaluated by a panel of experts. The fourth, fifth, and sixth steps of the model are dedicated to the implementation, monitoring, and evaluation of the program. CONCLUSION: It is expected that in the case of its effective implementation by social welfare and health organizations, the empowerment program would have the potential to have a considerable effect on reducing or controlling high-risk behaviors in adolescent girls with substance use disorder.